2021
DOI: 10.3390/su13179506
|View full text |Cite
|
Sign up to set email alerts
|

Research on Innovation Non-Equilibrium of Chinese Urban Agglomeration Based on SOM Neural Network

Abstract: Different indicators, such as the number of patent applications, the number of grants, and the patent conversion rate, were proposed in this study to analyze the issue of innovation imbalance within and between urban agglomerations from a new perspective. First, a preliminary analysis of the current state of innovation and development of China’s nine urban agglomerations was conducted. Then the Theil index, widely used in equilibrium research, was employed to measure the overall innovation gap of China’s urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…If only the lowest index, that is, the basic evaluation index, is considered as the input and the middle index is not considered, the whole evaluation system is regarded as a black box, and finally an output, that is, the benefit degree, is obtained. In this way, the whole evaluation system can be regarded as a black box of complex nonlinear functions, which actually has something in common with the mesh evaluation index system, and also conforms to the characteristics that human resource management is a large system with complex mechanism [21].…”
Section: Evaluation Methods Based On Som Neural Networkmentioning
confidence: 99%
“…If only the lowest index, that is, the basic evaluation index, is considered as the input and the middle index is not considered, the whole evaluation system is regarded as a black box, and finally an output, that is, the benefit degree, is obtained. In this way, the whole evaluation system can be regarded as a black box of complex nonlinear functions, which actually has something in common with the mesh evaluation index system, and also conforms to the characteristics that human resource management is a large system with complex mechanism [21].…”
Section: Evaluation Methods Based On Som Neural Networkmentioning
confidence: 99%
“…However, the difference was smaller in the multi-indicator classification results. This shows that China's urbanization is unbalanced [41][42][43]. Based on the classification results of the machine learning algorithm, it was found that this imbalance is manifested in many aspects, such as level of education.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that provincial capital cities have richer innovation resources and have accumulated a great deal of innovation experience, which continues to attract an inflow of talent and resources from neighboring cities, leading to a further increase in the innovation gap. In addition, the inequitable distribution of innovation resources by the government may also contribute to this phenomenon [72].…”
Section: Overview Of Findingsmentioning
confidence: 99%